2014
DOI: 10.1109/tla.2014.6827879
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Packet Error models in VANET simulations

Abstract: In this paper, we review the workflow of the channel and physical layer modules in VANET simulations and briefly survey some of the most used propagation and packet error models in network simulators for this kind of networks. Through numerical simulations, we compare these propagation models working with a realistic and straightforward packet error model. Our results indicate that there is not a propagation model more conservative than the others and that a model is conservative or not depending on the channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Numerical models were used in the comparison of these propagation models operating with realistic and simple packet error framework. The obtained results [12] suggested that no propagation models are more conservative than others, and that the frameworks are considered conservative based on the capacity of the channel. It is also worth noting that separate propagation frameworks specifically for VANETs, produce outputs that are very close to their intermediate capacities.…”
Section: A-deterministic Channel Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerical models were used in the comparison of these propagation models operating with realistic and simple packet error framework. The obtained results [12] suggested that no propagation models are more conservative than others, and that the frameworks are considered conservative based on the capacity of the channel. It is also worth noting that separate propagation frameworks specifically for VANETs, produce outputs that are very close to their intermediate capacities.…”
Section: A-deterministic Channel Modelmentioning
confidence: 98%
“…However, Ray tracing is often impractical due to the need for a detailed description of the specific propagation environment [11]. An earlier research study by [12] involved a recap of the channel workflows and the physical layer modules of the VANETs models, and a brief survey of the mostly utilised packet and propagation errors frameworks in the network simulators for this specific type of networks. Numerical models were used in the comparison of these propagation models operating with realistic and simple packet error framework.…”
Section: A-deterministic Channel Modelmentioning
confidence: 99%
“…As we showed in [10], any realistic propagation model can be used as a reference to compare other proposals, keeping the comparison results invariable. The reason is that specific propagation models designed for VANETs provide very close results with intermediate channel capacities.…”
Section: Realistic Vanet Channel Modelingmentioning
confidence: 99%
“…Figure 6. State of the channel and interference management of a wireless channel for a node in a network simulator [10].…”
Section: Operation Of Channel and Physical Modules In A Network Simulmentioning
confidence: 99%
“…This penalty factor follows a geometric distribution. The probabilities of a successful message reception for different path lengths were obtained from [22]. P d is the penalty factor for the disconnected nodes.…”
Section: Data Setsmentioning
confidence: 99%